Genetic risk for myocardial infarction determined by polymorphisms of candidate genes in a Japanese population. Issue 4 (12th December 2007) - Yamada, Y; Kato, K; Oguri, M; Fujimaki, T; Yokoi, K; Matsuo, H; Watanabe, S; Metoki, N; Yoshida, H; Satoh, K; Ichihara, S; Aoyagi, Y; et al.
Abstract : Background: Although several environmental factors influence the development of myocardial infarction (MI), genetic factors have been shown to contribute to individual susceptibility to this condition. Objective: To identify gene polymorphisms that confer susceptibility to MI in order to allow assessment of genetic risk for this condition. Methods: 3433 unrelated Japanese people (1931 men, 1502 women) were entered into the study. These comprised 1328 subjects with MI (1036 men, 292 women) and 2105 controls (895 men, 1210 women). The genotypes for 40 polymorphisms of 31 candidate genes were determined with a method that combines PCR and sequence-specific oligonucleotide probes with suspension array technology. Results: The χ 2 test revealed that six polymorphisms were significantly (false discovery rate <0.05) related to the prevalence of MI. Further examination by multivariable logistic regression analysis with adjustment for age, sex, body mass index and the prevalence of hypertension, diabetes mellitus and hypercholesterolaemia, in addition to a stepwise forward selection procedure found that the A→C (Gln1334His) polymorphism (rs3742207) of the collagen type IV alpha-1 gene ( COL4A1 ) and the A→G polymorphism (rs4804611) of the zinc finger protein 627 gene ( ZNF627 ) were significantly (p<0.05) associated with the prevalence of MI. The variant C allele of COL4A1 was protective against MI, whereas the variant G allele of ZNF627 represented a risk factor for this condition. Conclusions: Determination of genotypes for COL4A1 and ZNF627 may prove informative for assessment of the genetic risk for MI.